WAYS TO OVERCOME SPEECH DEFECTS IN THE EDUCATION OF PARALYZED CHILDREN - Makhmudov Khurshid Shukhratovich (Galaxy International Interdisciplinary Research Journal, 2023)
The article describes ways to overcome speech defects in the education of paralyzed children of the Foundation Movement and preliminary corrective measures aimed at expanding the child’s practical and emotional experience to develop the child’s vocabulary.